2021
DOI: 10.1002/lio2.647
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning in adults with oral cancer: Multi‐institutional cross‐sectional study

Abstract: Purpose: Patients undergoing head and neck surgery are often elderly and frail with significant comorbidities. Discussion and documentation of what patients would desire for end-of-life care and decision-making is, therefore, essential for delivering patient-centered care.Materials and Methods: This was a retrospective, cross-sectional study of patients undergoing surgery for head and neck cancer at two large, academic, tertiary care centers in Canada. Advance care planning was defined as any documentation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Fourteen articles that were not included in these categories are reported in Table 1. They address two topics: ACP uptake rates [39–44]; and ACP outcomes [45–52].…”
Section: Overview Of Factors Influencing Advance Care Planning Commun...mentioning
confidence: 99%
See 1 more Smart Citation
“…Fourteen articles that were not included in these categories are reported in Table 1. They address two topics: ACP uptake rates [39–44]; and ACP outcomes [45–52].…”
Section: Overview Of Factors Influencing Advance Care Planning Commun...mentioning
confidence: 99%
“…Thirty-eight studies [15–52] and three reviews were identified [6 ▪ ,8 ▪▪ ,13 ▪▪ ]. Studies were heterogeneous in terms of cancer care contexts, population size and characteristics, research designs, and assessment methods (Table 1).…”
Section: Literature Search and Samplementioning
confidence: 99%
“…However, Forner et al. [ 17 ] investigated the rate of preoperative ACP document signing in patients undergoing oral cancer surgery and found that the rate of preoperatively signing ACP documentation in this population was only 10.3%. On the one hand, this suggests the feasibility of applying ACP in patients undergoing HNC surgery; on the other hand, this also suggests that the views of stakeholders toward the implementation of ACP in patients undergoing HNC surgery need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%